Description of Student Responses to the Implementation of the Inquiry Learning Model in Physics - Jufrida Jufrida; Dwi Agus Kurniawan; Tanti Tanti; Weni Sukarni; Erika Erika; Roro Hoyi; Muhammad Ikhlas (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
The model of learning is one of the approaches of strategy that teachers must carry out in a systematic and procedural to regulate the activities of learning to achieve the goal of learning. The process of learning by using a model of learning inquiry can increase the activity of the students, the courage of students in revealing ideas and ideas, and improve students' science process skills in the physics learning process. The purpose of the research is to know how students' response to models of learning of inquiry was used at the time of learning physics and see whether the application of the model the students are more skilled in learning. Research is conducted in SMA Negeri 8 Muaro Jambi on student grade X IPA 1, which aims to determine students' response when given an inquiry learning model during the process of learning physics. The instrument that is used is a questionnaire of students with a sample of 21 students. This study used a mixed-method with a sequential explanatory design. The descriptive statistics were employed in the data analysis technique to obtain the average, mode, median, minimum, and maximum values. Based on the findings of this study, it is possible to conclude that using inquiry learning models in physics learning can boost student activity, independence, and science skills. This is demonstrated by the students' responses in quite good categories. Students feel accountable for formulating, analyzing, and solving problems when using the inquiry learning methodology. So that students can learn physics in a more meaningful way, and the material is easier to retain. The student response rate to the learning model is rated as satisfactory.